Feasibility study of a vapor chamber with a hydrophobic evaporator substrate in high heat flux applications. (August 2017) - Shaeri, Mohammad Reza; Attinger, Daniel; Bonner, Richard
Abstract: A novel vapor chamber was fabricated to assess the feasibility of combining hydrophobic and hydrophilic wettabilities in the evaporator to optimize thermal performance. The proposed vapor chamber included a separate layer of hydrophilic sintered copper powder wick that was pressed in intimate contact with a hydrophobic evaporator substrate with a water contact angle around 140°. The contact between the wick layer and the evaporator was provided by sixteen posts implemented on the condenser, which pushed the wick layer toward the evaporator. The thermal performance was evaluated based on the thermal resistance, source temperature, and temperature uniformity across the condenser. Results were compared with those of a baseline vapor chamber that was fabricated by sintering hydrophilic copper particles on a hydrophilic copper evaporator substrate. The wick size and the copper powders used to fabricate the wick structure were the same in both vapor chambers. Overall, the performance of the proposed vapor chamber was lower than that of the baseline vapor chamber, possibly due to microscale gaps between the wick layer and the evaporator substrate. However, the concept of using a hydrophilic wick to force liquid in contact with a hydrophobic evaporating surface could enable a new family of vapor chambers with low thermal resistance, if more efficient techniques for improving the mechanical contact between the wick layer and the evaporator are introduced through further detailed research. If successful, the fabrication cost of vapor chambers would be reduced as well, by using prepared wick structures, which do not require high-temperature sintering processes on evaporators.